2017
DOI: 10.1371/journal.pone.0188482
|View full text |Cite
|
Sign up to set email alerts
|

The importance of mean time in therapeutic range for complication rates in warfarin therapy of patients with atrial fibrillation: A systematic review and meta-regression analysis

Abstract: Background\Anticoagulation is used for stroke prophylaxis in non-valvular atrial fibrillation, amongst other by use of the vitamin K antagonist, warfarin. Quality in warfarin therapy is often summarized by the time patients spend within the therapeutic range (percent time in therapeutic range, TTR). The correlation between TTR and the occurrence of complications during warfarin therapy has been established, but the influence of patient characteristics in that respect remains undetermined. The objective of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
1
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 55 publications
(61 reference statements)
1
46
1
6
Order By: Relevance
“…It is well known that a myriad of factors can affect warfarin therapy . Among these factors, the quality of anticoagulation control has been shown to directly influence both efficacy and safety of warfarin . For Thailand, limited local data suggested that quality of anticoagulation control, as expressed by time in therapeutic range (TTR), is still suboptimal .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that a myriad of factors can affect warfarin therapy . Among these factors, the quality of anticoagulation control has been shown to directly influence both efficacy and safety of warfarin . For Thailand, limited local data suggested that quality of anticoagulation control, as expressed by time in therapeutic range (TTR), is still suboptimal .…”
Section: Introductionmentioning
confidence: 99%
“…1 Among these factors, the quality of anticoagulation control has been shown to directly influence both efficacy and safety of warfarin. 17 For Thailand, limited local data suggested that quality of anticoagulation control, as expressed by time in therapeutic range (TTR), is still suboptimal. 8 In addition, racial difference, higher level of anticoagulation needed for SPMVR, patterns of comorbidities, and overall health system quality may affect in the development of WAMB.…”
Section: Introductionmentioning
confidence: 99%
“…Warfarin requires ongoing monitoring of Internationalised Normalised Ratio (INR) due to a narrow therapeutic index and interactions with numerous drugs . The time in therapeutic range (TTR) is often used to indicate the quality of warfarin therapy due to the established correlation between higher mean TTR and reduced complications such as bleeding and thromboembolism . TTR is strongly associated with bleed risk, but increased bleeding with warfarin has also been associated with patient comorbidities and concurrent administration of other medication linked to bleeding including antiplatelet agents and non‐steroidal anti‐inflammatories (NSAIDs) .…”
mentioning
confidence: 99%
“…It is a strong predictor of adverse events in warfarin-treated patients such that lower TTR (<60%) is associated with an increased risk of major bleeding and thromboembolism. [14][15][16][17][18] TTR was calculated using the Rosendaal method as previously described 19 based on linear interpolation to infer the proportion of days a patient spent within his or her respective therapeutic range.…”
Section: Study Outcomesmentioning
confidence: 99%